Novel nanocomposites with advanced materials and their role in waste water treatment - Suchitra Kumari Panigrahy; Abhijeeta Nandha; Megha Chaturvedi; Priyesh Kumar Mishra (Next Sustainability)
Composites having minimum one phase with dimensions in the nanometer range are called nanocomposites. Materials made of nanocomposite have emerged as suitable alternatives to the absurd limitations of micro composites. Nanocomposites are advanced materials with wide range of application in many fields, from biomedical applications to packaging. They also have the potential to revolutionize wastewater treatment and energy harvesting processes. This current review explores the multifaceted applications of nanocomposites, specifically tailored for addressing the complex issues associated with water purification. The many varieties of matrix nanocomposites are discussed in this article, along with their importance, composition, characteristics, methods of processing, and applications in removing heavy metal, dyes, bacteria and dissolved gas from the contaminated water. Along with limitations, environmental impact of nanocomposites and future prospects of nanocomposites were highlighted. This will ensure future researchers to find novel nanocomposites with broad-spectrum applications.